Guest editor - Hadjielias, Elias (My University, 2026)
Guest editor of Special Issue on “Advancing Research Methodologies in Management Scholarship” https://onlinelibrary.wiley.com/pb-assets/assets/14678551/BJM%20Call%20for%20Papers%20Advancing%20Research%20Methodologies-1613746482.pdf